Trust, truth, and ridiculous goofs reading and writing friendship poems - Kalz, Jill (North Mankato, Minnesota Picture Window Books, [2014])
Introduces basic poetry forms and terms through the use of original friendship-themed poems
Rhymes
1 2 13 15
Keywords: Friendship -- Juvenile poetry; Poetry -- Authorship -- Juvenile literature; Poetry -- Authorship